Targeting Annexin A2 to reactivate tumor-associated antigens presentation and relieve immune tolerance in liver cancer - Min Li; Hui Shen; Feng Xie; Feng Lu; Jianxin Yang; Yuxiao Tang; Qicong Shen; Zelong Gao; Mengpu Wu; Chenghua Wu; Jicong Du; Changquan Ling; et al. (Journal for ImmunoTherapy of Cancer)
Background Tumor cells manipulate the tumor-associated antigens presentation to escape immune surveillance; however, the molecular mechanism is not exactly clear and the measure to intervene is missing.Methods Annexin A2 was knockout by the CRISPR-Cas9 or blocked by the small-molecule matrine, PY60, and hexapeptide. Chemically and genetically induced primary liver cancer models, and the orthotopically implanted liver tumor model were used. Tumor immune environment was analyzed by single-cell sequencing. Annexin A2-interacted proteins and tumor-associated antigens were identified by co-immunoprecipitation coupled with liquid chromatography with tandem mass spectrometry. Tumor cells killing effects were evaluated by co-culture of tumor cells and CD8+ T cells.Results Targeting Annexin A2 effectively suppressed the progression of liver cancer. The immunosuppressive microenvironment was improved by Annexin A2 inhibition in tumor tissues. The CD8+ T cells were increased and activated by targeting Annexin A2. Mechanistically, targeting Annexin A2 inhibited its combination with HSP90. The HSP90-mediated tumor-associated antigens presentation was recovered, and the major histocompatibility complex I-presented short peptides were changed, increasing the tumor cells killing by CD8+ T cells. Interestingly, Annexin A2 was increased in liver cancer tissues and the overall survival was significantly reduced in patients with high expression. However, Annexin A2 was positively correlated with immune cell infiltration in liver cancer, implying that Annexin A2 was used by tumor cells for immune escape and immunotherapy resistance. Hence, we further confirmed that blocking Annexin A2 increased the therapeutic effects of anti-programmed cell death protein-1 both in vitro and in vivo.Conclusions Taken together, our results identified the role of Annexin A2 in the tumor-associated antigens presentation and immune evasion, which could be an actionable target in cancer immunotherapy.